Therapeutic Potential of the Intestinal Microbiota for Immunomodulation of Food Allergies - Kreft, Luisa; Hoffmann, Christian; Ohnmacht, Caspar (Frontiers in Immunology, 2020)
Food allergy is an atopic disease that is caused by the immune system targeting harmless food antigens that can result in life-threatening anaphylaxis. As humans and microbes have co-evolved, inevitably commensal microbes have a tremendous impact on our health. As such, the gut with its enormous microbial richness reflects a highly tolerogenic environment at steady state, in which immune cells are educated to react in a well-calibrated manner to food and microbial antigens. Recent evidence indicates that the susceptibility to food allergy is critically linked to microbial dysbiosis and can be transmitted by microbial transfer from humans to mice. Experimental work and epidemiological studies further point towards a critical time window in early childhood during which the immune system is imprinted by microbial colonization. Particularly, Foxp3-expressing regulatory T cells turn out to be key players, acting as rheostats for controlling the magnitude of food allergic reactions. An increasing number of bacterial metabolites has recently been shown to regulate directly or indirectly the differentiation of peripherally induced Tregs, most of which co-express the RAR-related orphan receptor gamma t (RORγt). Genetic ablation provided additional direct evidence for the importance of RORγt+ Tregs in food allergy. Future strategies for the stratification of food allergic patients with the aim to manipulate the intestinal microbiota by means of fecal transplantation efforts, pre- or probiotic regimens or for boosting oral immunotherapy may improve diagnosis and therapy. In this review some of the key underlying mechanisms are summarized and future directions for potential microbial therapy are explored.